2018
DOI: 10.1016/j.mex.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Expert-based controllability assessment of control transitions from automated to manual driving

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…For example, prior research has suggested that the number of gaze switches (i.e., monitoring behavior) can serve as an indicator for trust/reliance [18], or interface understanding [29]. One solution to the difficulty and extensive effort of collecting behavioral data might be experimenters' single-item ratings of interaction performance [139][140][141]. However, this approach requires well-trained raters and, ideally, ratings are given single-blind, so that the rater is not aware of assigned experimental conditions for the participant.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…For example, prior research has suggested that the number of gaze switches (i.e., monitoring behavior) can serve as an indicator for trust/reliance [18], or interface understanding [29]. One solution to the difficulty and extensive effort of collecting behavioral data might be experimenters' single-item ratings of interaction performance [139][140][141]. However, this approach requires well-trained raters and, ideally, ratings are given single-blind, so that the rater is not aware of assigned experimental conditions for the participant.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…Both complexities and the familiarity are assumed to influence the takeover quality. The quality of the takeover is rated using the take-over controllability rating (TOC; [18]). The TOC is a procedure for an assessment of control transitions from automated to manual driving.…”
Section: Takeover Qualitymentioning
confidence: 99%
“…Endangerment is rated between seven and nine, including endangerment of others and self-endangerment over all the sub-scales. In cases of non-controllable events, the takeover is rated with a ten, including collision, lane departure/leaving road or loss of vehicle control over all the sub-scales [18]. Low values indicate a faultless takeover (= 1) and high quality.…”
Section: Takeover Qualitymentioning
confidence: 99%
“…Expert rating of takeover performance based on the video. For that the take-over controllability (TOC) rating was performed ( [27], for more details see https://toc-rating.de/en/) which defines a standardized procedure for the evaluation of take-over situations. Relevant dimensions for evaluation are provided with defined criteria for the different rating categories.…”
mentioning
confidence: 99%